Efficiency of cleaning and disinfection of surfaces: correlation between assessment methods - Oleci Pereira Frota; Adriano Menis Ferreira; Odanir Garcia Guerra; Marcelo Alessandro Rigotti; Denise de Andrade; Najla Moreira Amaral Borges; Margarete Teresa Gottardo de Almeida
ABSTRACT Objective: to assess the correlation among the ATP-bioluminescence assay, visual inspection and microbiological culture in monitoring the efficiency of cleaning and disinfection (C&D) of high-touch clinical surfaces (HTCS) in a walk-in emergency care unit. Method: a prospective and comparative study was carried out from March to June 2015, in which five HTCS were sampled before and after C&D by means of the three methods. The HTCS were considered dirty when dust, waste, humidity and stains were detected in visual inspection; when ≥2.5 colony forming units per cm2 were found in culture; when ≥5 relative light units per cm2 were found at the ATP-bioluminescence assay. Results: 720 analyses were performed, 240 per method. The overall rates of clean surfaces per visual inspection, culture and ATP-bioluminescence assay were 8.3%, 20.8% and 44.2% before C&D, and 92.5%, 50% and 84.2% after C&D, respectively (p<0.001). There were only occasional statistically significant relationships between methods. Conclusion: the methods did not present a good correlation, neither quantitative nor qualitatively.